Lithium fluoride dissolution in sulfuric acid solution: Optimization and application in the extraction of lithium from fluorinated α-spodumene - Resentera Beiza, Alexander Cristian Jesús; Rosales, Gustavo Daniel; Esquivel, Marcelo Ricardo Oscar; Rodriguez, Mario Humberto (Elsevier Science, 2023)
Fil: Resentera Beiza, Alexander Cristian Jesús. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina